Pyoderma Gangrenosum - Variants And Associations - Sentamilselvi G; Manoharan K; Saraswath Devesh; Janaki V.R (Wolters Kluwer Medknow Publications, 2002)
Six cases of pyoderma gangrenosum encountered with in a period of 2 years are described here with their clinical presentations and associations. Three patients were cases of superficial granulomatous pyoderma and three were of ulcerative type. Rheumatoid arthritis was found to be the associated disease in one of the cases of ulcerative type. Response to therapy was satisfactory in all of them expect in one case of ulcerative pyoderma gangrenosum who was resistant to most of the available therapeutic modalities.